Personal, Economic, and Societal Factors Affecting the Anxiety of Traders during the COVID-19 Pandemic in the Lower Northeastern Region of Thailand - Pheunpha, Pichyada (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The objectives of this research were to 1) study the anxiety levels of traders during the first wave of the COVID-19 epidemic. 2) To study personal factors, socio-economic factors affect traders' anxiety during the COVID-19 epidemic. Samples were 157 sub-districts from 559 sub-districts by purposive sampling method in 4 provinces in the lower northeastern region, namely Ubon Ratchathani, Amnat Charoen, Sisaket, and Yasothon. The respondents in the sample were 3,561 people who traded in these 157 sub-districts in the four lower northern Isan provinces: survey research and a questionnaire with a reliability of 0.87 were used in this study. Data analyses were descriptive statistics and multiple linear regression. The research found that the traders' anxiety was at a moderate level. They were afraid of COVID-19, followed by they had no spare to spend on the COVID-19 situation. Next, the business could not proceed with the COVID-19 epidemic, and they could not adapt to the new normal at a high level. Other anxieties were at a low level. The MLR results showed that R = 0.398, the independent variables and traders' anxiety, were moderate-level. R2=.15.5 means the independent variables can variation the anxiety traders by 15.5 percent. The positive influencing variables are 1) awareness of the cost of COVID treatment. 2) Perception of community news information about opening-closing of business. 3) The perception of the governor's declaration communication to close-open business. 4) The loan business, 5) lower-income, and 6) health expenses. The influencing variables that decrease anxiety were: 1) electricity bill, 2) monthly income, 3) age, and 4) travel expenses, respectively.